The relationship between red blood cell distribution width and atrial fibrillation in Asian population: A cross‐sectional study. Issue 9 (20th August 2019) - Li, Huiping; Gu, Yeqing; Liu, Mingyue; Wang, Xiaona; Chi, Vu Thi Quynh; Zhang, Qing; Liu, Li; Meng, Ge; Yao, Zhanxin; Wu, Hongmei; Bao, Xue; Zhang, Shunming; et al.
Abstract: Background: Red blood cell distribution width (RDW) was related with increased risk of mortality and adverse cardiovascular outcomes. However, it is uncertain whether RDW is related to the prevalence of atrial fibrillation (AF) in Asian population. The aim of this study was to assess the relationship between RDW and AF in a large Chinese population. Methods: We performed a cross‐sectional study to examine the relationship between RDW and AF among 106 998 subjects who were from the Tianjin Chronic Low‐grade Systemic Inflammation and Health Cohort Study. AF was diagnosed using electrocardiography, and RDW was measured using an automated hematology analyzer. Multiple logistic regression models were conducted to examine the relation between tertiles of RDW and AF. Results: The overall prevalence of AF was 0.1% (129/106 998). After adjustments for potential confounding factors, the odds ratios (95% confidence intervals) of AF across increasing tertiles of RDW were 1.00 (reference), 1.08 (0.69, 1.67), and 2.65 (1.75, 4.07) ( P for trend < .0001), respectively. Conclusions: The study demonstrated that elevated RDW is significantly related to higher prevalence of AF in a general Chinese population. Large prospective studies are needed to confirm this finding.